The Effects of Gas Diffusion in Molten Carbonate Fuel Cells Working as Carbon Capture Devices. Issue 11 (31st July 2020) - Audasso, E.; Bosio, B.; Bove, D.; Arato, E.; Barckholtz, T.; Kiss, G.; Rosen, J.; Elsen, H.; Blanco Gutierrez, R.; Han, L.; Geary, T.; Willman, C.; et al.
Abstract : Molten Carbonate Fuel Cells (MCFCs) are used in MW-scale power plants. Recently, they have also been explored for carbon capture. A recent MCFC experimental campaign for carbon capture applications has shown interesting results. It revealed that at carbon capture conditions a secondary reaction mechanism involving hydroxide ions starts to affect cell performance. This is important since part of the electricity produced will be used to transfer water instead of CO2, decreasing capture efficiency. Previously, the authors developed a dual-ion model for MCFCs to account for the observed loss of carbon capture efficiency at low-CO2 cathode gas conditions. A more recent, deeper exploration of MCFC control parameters found that the split between the competing reaction paths depends not only on the cathode gas composition, but also on cathode diffusion resistance. Thus, in this work we increase the applicability range and reliability of the dual-ion electrochemical model by including the diffusion of reactants in the porous cathode along the axis perpendicular to the cell plane. This transport component can account for the shifting of carbonate and hydroxide contributions to the overall cell current as a function of cathode feed properties and for different current collector designs that determine the diffusion resistance term.